Biogenic amine content in various types of tofu: occurrence, validation and quantification - Yue, C. S. (2021)
In the present work, the biogenic amines tryptamine (TRP), putrescine (PUT), histamine (HIS), tyramine (TYR) and spermidine (SPD) were determined in 32 various types of tofu that were obtained from different states in Malaysia. Three main types of tofu; soft tofu, firm tofu and processed tofu, were analysed in the present work. The biogenic amine contents in the respective types of tofu were analysed by a reversed-phase HPLC with a DAD detector after the aqueous extraction and derivatisation with dansyl chloride. The LOD values ranged from 0.019 mg/L for PUT to 0.028 mg/L for TYR. While, the LOQ values ranged from 0.063 mg/L (PUT) to 0.096 mg/L (TYR). The recovery values for all the five amines ranged from 80.3% to 120.5% with RSD ≤ 3.1%. The total levels of biogenic amines found varied, ranging from 1.5 mg/kg to 687.9 mg/kg, with mean values (p < 0.05) in descending order of 44.6, 12.6, 9.1, 4.8 and 4.7 mg/kg for PUT, TYR, SPD, HIS and TRP, respectively. PUT and TRP were the most prevailing biogenic amines and they were found respectively in 90.62% of the tofu analysed. Significant positive correlations (r = 0.266 to 0.874, p < 0.05) were found between some individual biogenic amines and protein content in all the three types of tofu. However, negative correlations (r = -0.246 to -0.832, p < 0.05) were observed between biogenic amines and moisture content, and between biogenic amines and water activity in all the three types of tofu. Significant and strong correlations (r = 0.525 to 0.999, p < 0.05) were found between most of the individual biogenic amines and the total biogenic amines. Those tofu exceeding the legal limits may affect the health of sensitive individuals.